1997
DOI: 10.1002/anie.199714891
|View full text |Cite
|
Sign up to set email alerts
|

The Surprising Crystal Packing of Chlorinefluoride

Abstract: Infinite ribbons with only very short intermolecular ClCl contacts, and not dipole–dipole interactions, characterize the crystal packing of ClF (depicted on the right). The explanation for this surprising finding is that chlorine in ClF may act simultaneously as an electron donor and acceptor, as shown by the experimental Laplacian charge density maps and ab initio calculations for the CIF dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
5

Year Published

2001
2001
2005
2005

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 30 publications
2
41
0
5
Order By: Relevance
“…We start by generating crystal structures of the n-alkanes, using the experimentally available x-ray structures. [33][34][35][36][37][38] Table II contains the cell parameters of the alkanes, which were used to generate initial alkane crystals. Dispersion forces are exquisitely sensitive to the intermolecular distances, and the present computations are very sensitive to the adopted cell parameters of the host lattices; good x-ray data are in fact a prerequisite for successful modeling.…”
Section: B Computational Methodology: Molecular Mechanics and Dynamimentioning
confidence: 99%
“…We start by generating crystal structures of the n-alkanes, using the experimentally available x-ray structures. [33][34][35][36][37][38] Table II contains the cell parameters of the alkanes, which were used to generate initial alkane crystals. Dispersion forces are exquisitely sensitive to the intermolecular distances, and the present computations are very sensitive to the adopted cell parameters of the host lattices; good x-ray data are in fact a prerequisite for successful modeling.…”
Section: B Computational Methodology: Molecular Mechanics and Dynamimentioning
confidence: 99%
“…This so-called polar flattening has been used to explain why there are close intermolecular halogenÁ Á Áhalogen contacts. Allen et al have shown, however, that intermolecular contacts between the halogen (Cl, Br, and I) and the electronegative (O, N) atoms can exist [16] and strong intermolecular halogenÁ Á Áhalogen interactions have been, for example, reported for chlorinemonofluoride [17].…”
Section: Introductionmentioning
confidence: 95%
“…High-quality experimental densities of minerals, 12-20 covalent, 21 metallic, 22 and molecular crystals [23][24][25][26][27] have been analyzed in terms of AIM concepts. In addition, theoretical calculations on simple metals, [28][29][30] alloys and intermetallic phases, [31][32][33][34][35][36][37][38][39][40] molecular, 10,30,41,42 covalent, and ionic crystals, 11,20,21,30,[43][44][45][46][47][48][49] as well as impurity centers and defects [50][51][52][53] have been reported.…”
Section: Introductionmentioning
confidence: 99%